2018
DOI: 10.1111/dom.13574
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, randomized clinical trial comparing the efficacy and safety of continuing or discontinuing the dipeptidyl peptidase‐4 inhibitor sitagliptin when initiating insulin glargine therapy in patients with type 2 diabetes: The CompoSIT‐I Study

Abstract: Aims To compare the effects of continuing versus discontinuing sitagliptin when initiating and intensively titrating insulin glargine. Materials and methods Eligible patients had inadequately controlled type 2 diabetes on metformin (≥1500 mg/d) in combination with a dipeptidyl peptidase‐4 (DPP‐4) inhibitor and/or a sulphonylurea. Those on metformin + sitagliptin were directly randomized; all others were switched to metformin + sitagliptin (discontinuing other DPP‐4 inhibitors and sulphonylureas) and stabilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…In a study of patients with T2D and in which a DPP-4i was added therapy was intensified for DPP-4i compared with placebo. In another randomized control trial, continuation of a DPP-4i when initiating basal insulin was shown to be associated with better glycemic control (mean HbA1c and least squares (LS) mean change from baseline in HbA1c were 6.85 and À1.88% in the treatment group and 7.31 and À1.42% in the placebo group), a lower daily insulin dose (53 vs. 61 units), and no difference in the incidence of hypoglycemia after 30 weeks 5 . The cost of DPP-4i in addition to insulin was also reported as a potential reason for discontinuation which would be less of an issue outside the US where, for example in the UK, patients do not contribute to the costs of their anti-diabetes medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of patients with T2D and in which a DPP-4i was added therapy was intensified for DPP-4i compared with placebo. In another randomized control trial, continuation of a DPP-4i when initiating basal insulin was shown to be associated with better glycemic control (mean HbA1c and least squares (LS) mean change from baseline in HbA1c were 6.85 and À1.88% in the treatment group and 7.31 and À1.42% in the placebo group), a lower daily insulin dose (53 vs. 61 units), and no difference in the incidence of hypoglycemia after 30 weeks 5 . The cost of DPP-4i in addition to insulin was also reported as a potential reason for discontinuation which would be less of an issue outside the US where, for example in the UK, patients do not contribute to the costs of their anti-diabetes medication.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with T2D and inadequate control on insulin (with or without metformin) in which a DPP-4i was added and insulin therapy was intensified, a lower event rate (1.7 vs. 3.6 events/participant-year) and incidence of symptomatic hypoglycemia (25.2 vs. 36.8%; p ¼ .001) was observed for DPP-4i compared with placebo 9,10 . In another randomized control trial, continuation of a DPP-4i when initiating basal insulin was shown to be associated with better glycemic control (mean HbA1c and least squares (LS) mean change from baseline in HbA1c were 6.85% and À1.88% in the treatment group and 7.31 and À1.42 in the placebo group), a lower daily insulin dose (53 vs. 61 units), and no difference in the incidence of hypoglycemia after 30 weeks 5 . In a study of patients with T2D and in which a DPP-4i was added therapy was intensified for DPP-4i compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a scenario analysis tests the point estimates of the hazard ratios for cardiovascular events relative to placebo for the initial step in therapy from the CVOT studies. MET + SIT 100 mg [22] Weighted oral SEM a [22,23] MET + oral SEM 14 mg + IG [30,31] MET + SIT 100 mg + IG [30,31] MET + IG a [30,31] MET + IG + bolus insulin a [32,33] HbA1c, % −…”
Section: Intervention Effectsmentioning
confidence: 99%
“…Inhibitors of dipeptidyl peptidase‐4 (DPP‐4) are commonly employed as dual‐ or triple‐combination therapy in type 2 diabetes. Recent studies have shown the benefit of continuing these molecules when initiating insulin, allowing for a greater reduction in HbA1c of −5.0 mmol/mol and a decrease in insulin daily doses of −8.0 IU/day versus placebo, without increasing the number of hypoglycaemic episodes. DPP‐4 inhibitors are eliminated by up to 75% by the kidneys and, therefore, require dose adjustment in patients with chronic renal disease, except for linagliptin, which is not currently available in France.…”
Section: Introductionmentioning
confidence: 99%